The Principles Of Good Governance In Health Services - Marif, Marif; Nurhaedah, Nurhaedah; Bakhtiar, Handar Subhandi (Universitas Negeri Gorontalo, 2021)
This study provides an overview of the principles of good governance in health services in Indonesia. This needs to be known considering that health services are a constitutional right for citizens and their services must be carried out as well as possible. Providing health services is a state obligation and getting good and guaranteed health services are the right of citizens. This research is normative-legal research using statute, comparative and conceptual approaches. The results show the principles of good governance in health services that are reflected in the principles of participation, the principles of openness and transparency, the principles of effectiveness and efficiency, and the principles of accountability. Providing health services and covering all health insurance costs for the poor and underprivileged will automatically unconditionally be the responsibility of the government following the mandate of the constitution.